Butyrylcholinesterase as a prognostic marker: a review of the literature. Issue 1 (6th September 2012) - Santarpia, Lidia; Grandone, Ilenia; Contaldo, Franco; Pasanisi, Fabrizio
Abstract : Background: Butyrylcholinesterase (BChE) is an α‐glycoprotein synthesized in the liver. Its serum level decreases in many clinical conditions such as acute and chronic liver damage, inflammation, injury and infections, and malnutrition. Methods and results: This review collects the main evidence on the emerging role of butyrylcholinesterase as a prognostic marker of liver and nonliver diseases as well as a marker of protein‐energy malnutrition and obesity. In fact, serum concentrations and BChE activity seem to accurately reflect the availability of amino acidic substrates and/or derangement in protein synthesis due to hepatocellular damage. In cancer, with or without liver impairment, serum BChE levels serve as an accurate functional and prognostic indicator, useful for monitoring clinical and therapeutic interventions according to patients' prognosis. In the absence of inflammation, BChE could also serve as an index of the effectiveness of nutritional support. Conclusions: Serum BChE assessment should be included in routine clinical diagnostic procedures to evaluate patient clinical conditions, in particular in cases of inflammation and/or protein‐energy malnutrition.